The origins of Roman Christian diplomacy: Constantius II and John Chrysostom as innovators - Stevenson, Walter (Routledge, 2021)
"This book illuminates the origins of Roman Christian diplomacy through two case studies: Constantius II's imperial strategy in the Red Sea; and John Chrysostom's ecclesiastical strategy in Gothia and Sasanian Persia. Both men have enjoyed a strong narrative tradition: Constantius as a persecuting, theological fanatic, and Chrysostom as a stubborn, naïve reformer. Yet this tradition has often masked their remarkable innovations. As part of his strategy for conquest, Constantius was forced to focus on Alexandria, demonstrating a carefully orchestrated campaign along the principal eastern trade route. Meanwhile, whilst John Chrysostom' s preaching and social reform have garnered extensive discussion, his late sermons and letters composed in exile reveal an ambitious program to establish church structures outside imperial state control. The book demonstrates that these two pioneers innovated a diplomacy that utilised Christianity as a tool for forging alliances with external peoples; a procedure that would later become central to Byzantine statecraft. It will appeal to all those interested in medieval history"--